Implementation of Planning and Budgeting as a Business Development Strategy: A Case Study of Pataya 'Thai Tea' Shop - Nur abdi, Muhammad; Syah, Firman; Muhammad Iqram (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to provide an understanding of the implementation of planning and budgeting in the context of developing the Pataya "Thai Tea" shop as a business development strategy. The research was descriptive qualitative. The results showed that the Thai Tea beverage business has very good opportunities, this is indicated by the large number of enthusiasts who like this drink, ranging from children to adults. Supporting driving factors are strategic sales locations, attractive packaging, and achieving the desired target market. The process of preparing and implementing the Pataya Shop business development budget is considered to be in accordance with the four stages of budgeting (determining guidelines, preparation, determination, and implementation of the budget). The business development strategy of Mas Joe, the owner of Pataya Shop, focuses on expanding the business scale (additional branches). Capital for business development comes from own capital collected from setting aside daily income. The components of the cost budget prepared in the context of business development include premises, equipment, and supplies. This strategy is also supported by marketing, such as adding flavor variants and providing hangout spots, which have been proven to stabilize income amidst competition. With a controlled budget planning and implementation process that directly involves the owner, budget realization is considered not to deviate far from what was planned.